Mercury in the Environment : Pattern and Process - Bank, Michael S. (Book collections on Project MUSE., 2012)
Mercury pollution and contamination are widespread, well documented, and continue to pose a public health concern in both developed and developing countries. In response to a growing need for understanding the cycling of this ubiquitous pollutant, the science of mercury has grown rapidly to include the fields of biogeochemistry, economics, sociology, public health, decision sciences, physics, global change, and mathematics. Only recently have scientists begun to establish a holistic approach to studying mercury pollution that integrates chemistry, biology, and human health sciences. Mercury in.